Energetic nuclear transients in luminous and ultraluminous infrared galaxies - Reynolds TM; Mattila S; Efstathiou A; Kankare E; Kool E; Ryder S; Pena-Monino L; Perez-Torres MA (EDP SCIENCES S A, 2022)
Energetic nuclear outbursts have been discovered in luminous and ultraluminous infrared galaxies (U/LIRGs) at unexpectedly high rates. To investigate this population of transients, we performed a search in mid-IR data from the Wide-field Infrared Survey Explorer (WISE) satellite and its NEOWISE survey to detect and characterise luminous and smoothly evolving transients in a sample of 215 U/LIRGs. We report three new transients, all with ΔL >  1043 erg s−1, in addition to two previously known cases. Their host galaxies are all part of major galaxy mergers, and through radiative transfer model fitting we find that all have a significant contribution from an active galactic nucleus (AGN). We characterised the transients through measurements of their luminosities and resulting energetics, all of which are between 1050.9 erg and 1052.2 erg. The IR emission of the five transients was found to be consistent with re-radiation by the hot dust of emission at shorter wavelengths, presumably originating from an accretion event, onto the supermassive black hole. The corresponding transient rate of (1.6–4.6) × 10−3 yr−1 galaxy−1 is over an order of magnitude higher than the rate of large amplitude flares shown by AGN in the optical. We suggest that the observed transients are part of a dust-obscured population of tidal disruption events (TDEs) that have remained out of the reach of optical surveys due to the obscuring dust. In one case, this is supported by our radio observations. We also discuss other plausible explanations. The observed rate of events is significantly higher than optical TDE rates, which can be expected in U/LIRG hosts undergoing a major galaxy merger with increased stellar densities in the nuclear regions. Continued searches for such transients and their multi-wavelength follow-up is required to constrain their rate and nature.